Pendampingan Sertifikasi Halal bagi Pelaku UMKM sebagai Upaya Peningkatan Daya Saing Produk di Kecamatan Grabag, Kabupaten Magelang - Fazira Zulia Fata; Dakusta Puspitasari (khidmatan, 2026)
Halal certification is an important factor in improving product quality, consumer trust, and the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). However, many MSME owners still face challenges in understanding the procedures and requirements for obtaining halal certification. This community service program aimed to enhance the knowledge and capacity of MSME owners regarding the halal certification process in Grabag District, Magelang Regency. The program employed the Asset-Based Community Development (ABCD) approach, which focuses on utilizing community assets and potentials. The stages of the program included discovery (identification of MSME assets and potentials), dream (formulation of shared goals and expectations), design (planning of the assistance program), define (implementation of halal certification assistance), and destiny (evaluation and sustainability of the program). The activities were carried out through socialization, consultation, administrative assistance, and facilitation of halal certification applications. The results indicated an improvement in participants' understanding of the importance of halal certification, application procedures, and its benefits in enhancing consumer trust and product competitiveness. This assistance program contributed positively to supporting the development of more competitive, independent, and sustainable MSMEs in Grabag District, Magelang Regency.